Application of Selective Bronchial Intubation versus Neurally Adjusted Ventilatory Assist in the Management of Unilateral Pulmonary Interstitial Emphysema: An Illustrative Case and the Literature Review - Lee, Shing-yan Robert (American Journal of Perinatology Reports, 2017)
In the treatment of left-sided pulmonary interstitial emphysema (PIE) in a 23-week neonate, we used two ventilatory strategies: selective bronchial intubation from day 10 to 15 and neurally adjusted ventilatory assist (NAVA) from day 18 to 26. We compared the effects and adverse effects of these two strategies. On selective bronchial intubation, desaturation was frequent. Fentanyl infusion was required. There was an episode of carbon dioxide retention coupled with hypotension. On NAVA, the neonate was clinically stable without the requirement of sedation. On selective bronchial intubation, ventilator setting in terms of mean airway pressure and oxygen requirement was higher, which came down on the first day of NAVA. Radiologically unilateral PIE did not resolve and became localized in the left middle zone of lung field on selective bronchial intubation. Also, the lobar collapse of ipsilateral, as well as contralateral lungs occurred. On NAVA, unilateral PIE resolved. NAVA might be a good option for the management of unilateral PIE.
Keywords: unilateral pulmonary interstitial emphysema; prematurity; neonate; selective bronchial intubation; neurally adjusted ventilatory assist; NAVA